The Moderate Effect of Good Corporate Governance on Carbon Emission Disclosure and Company Value - Jhon Urasti Blesia; Enggelina Trapen; Rama Soyan Arunglamba (The Indonesian Journal of Accounting Research, 2023)
This research examines the influence of carbon emission disclosure on the firm value with good corporate governance as a moderating variable. A total of 20 Indonesian energy service companies listed on Indonesia's stock exchange in 2015-2021 are analyzed using the Moderated Regression. The results show a significant positive effect between carbon emission disclosure and firm value. Despite an increase in the carbon emission disclosures following the amendment of Indonesia Financial Accounting Standards of Number 1 in 2014 about the demands of environmental disclosures, good corporate governance in these companies cannot moderate the relationship between carbon emission disclosure and firm value. This research strengthens the legitimacy theory that environmental disclosure maintains the good reputation of the companies. Investors can consider carbon emission disclosure when determining their investment decisions. Management can determine companies' policies related to carbon emission disclosures. The results of this research can be regarded as determining policies related to reducing carbon and greenhouse gas emissions in Indonesia.